Chinese Guidelines for the Diagnosis and Treatment of Urticaria: 2018 Update - Center for Urticaria Research, Chinese Society of Dermatology∗ (Wolters Kluwer Health, 2020)
Abstract. Urticaria is a common dermatological condition that is characterized by wheals and pruritus. Certain types of urticaria can be resistant to treatment, and recurrence is common. These guidelines supplement and improve upon the previous version (published in 2014) of the Guidelines for the Diagnosis and Treatment of Urticaria in China, and incorporate recent research advances in urticaria. These guidelines are suitable for both Chinese adults and children of Han nationality with urticaria. These guidelines update and broaden the definition, pathogenesis, classification, diagnosis, and treatment of urticaria, and serve as a scientific and authoritative reference for the diagnosis and management of urticaria.